THE ANDRO-METABOLIC SIGNATURE OF IIH COMPARED WITH PCOS AND SIMPLE OBESITY. Issue 12 (15th November 2016) - Hornby, Catherine; O'Reilly, Michael; Botfield, Hannah; Markey, Keira; Kempegowda, Punith; Taylor, Angela; Hughes, Beverley; Tomlinson, Jeremy; Arlt, Wiebke; Sinclair, Alexandra
Abstract : Idiopathic intracranial hypertension (IIH) is a disorder of raised intracranial pressure (ICP) of unknown cause. This condition is primarily seen in obese females of childbearing age, a phenotype similar to that in polycystic ovary syndrome (PCOS). We aimed to characterise the androgen metabolic signature in IIH compared to PCOS and simple obese controls. Age, gender and BMI matched groups of IIH (n=25), PCOS (n=31) and obese controls (n=15) were studied. The IIH group also underwent a weight loss intervention. Serum androgens were measured by liquid chromatography/tandem mass spectrometry (LCMS) and urinary steroids using gas chromatography/mass spectrometry (GCMS). Serum testosterone was significantly higher in IIH and PCOS than in controls (p=0.01). Serum androstenedione was significantly increased in PCOS compared to IIH and controls (p=0.008). Systemic 5a-reductase activity was significantly higher in IIH compared to controls (p=0.04). Following weight loss there were significant reductions in testosterone, 5a-reductase activity and disease activity (intracranial pressure and papilloedema). These results demonstrate a unique androgen metabolic signature in IIH (distinct from PCOS and simple obesity), characterised by increased testosterone but normal androstenedione, potentially driven by increased AKR1C3 activity (which converts androstenedione to its active metabolite testosterone). Further evaluation of AKR1C3 in IIH would be of interest.